Factors that influence human errors in modern manufacturing processes - Salas-Arias, Karla Melissa (2018)
In the current industry, mechanized production processes are carried out, with defined parameters for these actions to be carried out by the operators. However, a deviation from these parameters is considered a human error, causing the disturbance of the production process. The article is elaborated with the purpose of identifying errors in the productive process of a Metalworking company with the joint action of the Laboratory of Ergonomics of the Technological Institute of Costa Rica. The identification of human errors was based on the Technique for human error-prediction (THERP) methodology; this analysis was complemented with a methodology of classification adapted for the administration of industrial processes called ABC methodology, 123 methodology and alfa beta range methodology to identify the critical errors for the company. Once these errors were identified, by means of an event tree the percentage was quantified by means of theoretical probabilities reported by the THERP literature and with this the percentage of affectation for the production process was analyzed. With this applied methodology, it was possible to identify in the company 26 errors in total.